PEMBUATAN MODEL PENILAIAN INDEKS KINERJA DOSEN MENGGUNAKAN METODE FUZZY MULTI ATTRIBUTE DECISION MAKING (FMADM) (Studi : PTS di Provinsi Lampung) - Andreas Andoyo; Muhamad Muslihudin; Noca Yolanda Sari (IIB Darmajaya, 2017)
Lecturers are one of the most important components in a college education system. Roles, duties, and responsibilities are very important in realizing national education that is the intellectual life of the nation to improve the quality of Indonesian people, which includes the quality of faith / noble, noble character, and mastery of science, technology and art, and realize the Indonesian society forward, prosperous, and civilized. Fuzzy Multi-Attribute Decision Making Method is one of the methods in decision making where alternatives are known and predetermined. Decision-making should determine priorities, weights, or rankings based on given criteria. to facilitate the evaluation of lecturer performance based on the tri dharma of universities covering pedagogic, professional, personality and social competence, the lecturer performance index is evaluated using Fuzzy Multi-Attribute Decision-Making method. The purpose of this research is to get the decision-making model of lecturer performance index using the Fuzzy Multi-Attribute Decision-Making method with predetermined criteria such as classroom study, GBP and sap stipulations, time conformity, material absorption, learning media, archive as, research, translation, lecturer activities. It is expected that the lecturer performance appraisal model can trigger lecturers to improve performance and facilitate the leadership to evaluate the performance of lecturers to improve the quality and quality of universities. Keywords: FMADM, Lecturer, Lecturer Performance